The effects of whey and pumpkin seed oil on blood biochemical parameters of liver function and lipid profile in rats chronically drinking low concentrations of ethanol - Radić Ivan; Nestorović Vojkan; Mijović Milica; Tatalović Nikola; Joksimović Bojan; Lukić Vera; Mitić Miloš; Adžić Miroslav; Blagojević Duško; Veličković Stefan; Bulajić Sonja; Đerković Branislav; et al. (Archives of Biological Sciences, 2018)
We studied the effects of whey and pumpkin seed oil supplementation on the biochemical parameters in blood serum of male rats after chronic ad libitum alcohol consumption. The levels of AST, ALT, total bilirubin, ALP, LDH, triglycerides, total cholesterol, HDL, LDL, VLDL, triglyceride/HDL ratio, total cholesterol/HDL ratio (cholesterol ratio) and LDL/HDL ratio (index of atherosclerosis) were determined in rats after six weeks of treatment with: (i) ethanol (12% ethanol, ad libitum), (ii) whey (2 g/kg per day), (iii) pumpkin seed oil (2 mL/kg per day), (iv) both ethanol and whey, and (v) both ethanol and pumpkin seed oil. The results showed no changes in the levels of AST, ALT, total bilirubin, ALP, total cholesterol, HDL and VLDL in alcoholic rats when compared to the controls (fed with a standard laboratory diet ad libitum) and rats supplemented with whey and pumpkin seed oil. Our results suggest that alcohol consumption in small doses for 6 weeks changes lipid metabolism and significantly elevates the LDL/HDL ratio (index of atherosclerosis) but does not induce extensive liver damage. Ethanol consumption in our experimental conditions lowered the triglyceride level as well as the triglyceride/HDL ratio, suggesting lipid redistribution and the induction of some cardio-protective effect. However, ethanol induced a higher index of atherosclerosis. Pumpkin seed oil showed some protective potential in alcoholic rats by lowering the total cholesterol/HDL ratio, but it elevated the LDH. Whey consumption prevented elevation of the atherosclerosis index, pointing to its protective role, probably through the redistribution of lipids. However, whey in combination with ethanol elevated LDH. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 173014 and Grant no. III41029]